Identities for homogeneous utility functions (2010)
Using a homogeneous and continuous utility function that represents a household's preferences, this paper proves explicit identities between most of the different objects that arise from the utility maximization and the expenditure minimization problems. The paper also outlines the homogeneity properties of each object. Finally, we show explicit algebraic ways to go from the indirect utility function to the expenditure function and from the Marshallian demand to the Hicksian demand and vice versa, without the need of any other function, thus simplifying the integrability problem avoiding the use of differential equations.